2021
DOI: 10.3390/ma14205956
|View full text |Cite
|
Sign up to set email alerts
|

An Injectable Chitosan-Based Self-Healable Hydrogel System as an Antibacterial Wound Dressing

Abstract: Due to their biodegradability and biocompatibility, chitosan-based hydrogels have great potential in regenerative medicine, with applications such as bacteriostasis, hemostasis, and wound healing. However, toxicity and high cost are problems that must be solved for chitosan-based hydrogel crosslinking agents such as formaldehyde, glutaraldehyde, and genipin. Therefore, we developed a biocompatible yet cost-effective chitosan-based hydrogel system as a candidate biomaterial to prevent infection during wound hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Compared to nano-vesicular structures such as liposomes and niosomes, emulgels offer better loading capacity due to networks formed by a gelling agent, and are also easier to prepare, since their production does not require special equipment [17]. The benefits of releasing active substances from emulgels have been investigated in many studies, which has led to the wide application of emulgels in the medical and cosmetic field [29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to nano-vesicular structures such as liposomes and niosomes, emulgels offer better loading capacity due to networks formed by a gelling agent, and are also easier to prepare, since their production does not require special equipment [17]. The benefits of releasing active substances from emulgels have been investigated in many studies, which has led to the wide application of emulgels in the medical and cosmetic field [29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The primary raw materials for the hydrogel preparation are chitosan and aldehyde chitosan. Due to the antibacterial activity of chitosan and aldehyde chitosan in the hydrogel network, the hydrogel system can significantly inhibit the growth of bacteria upon contact, making it an excellent candidate for antibacterial wound dressing [ 159 ]. Zhang et al developed a new antibacterial hydrogel wound dressing composed of poly(aminoethyl) modified chitosan (PAEMCS).…”
Section: Classification and Mechanism Of Antibacterial Hydrogelsmentioning
confidence: 99%
“…The results showed that the antibacterial properties of chitosan and aldehyde chitosan exhibited in the hydrogel system significantly impaired bacterial growth upon contact. 85 However, the antibacterial mechanism of chitosan and its derivatives is still not clear. There is a generally accepted theory that the large number of positively charged amino groups in their molecular structure plays a vital role, they can also absorb bacteria and enter bacterial cells to inhibit bacterial growth by interfering with the transcription of bacterial DNA and block the absorption of trace elements and nutrients necessary for cell growth.…”
Section: Biopolymer-based Antibacterial Hydrogelsmentioning
confidence: 99%